2010
DOI: 10.1002/jez.b.21338
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐dependent phenotypic variation of molluscan shells: implications for allometric data interpretation

Abstract: In recent years, developmental plasticity has received increasing attention. Specifically, some studies highlighted a possible association between shell shape and growth rates in intertidal gastropods. We use a growth vector model to study how hypothetical growth processes could underlie developmental plasticity in molluscs. It illustrates that variation in instantaneous shell growth rate can induce variability in allometric curves. Consequently, morphological variation is time-dependent. Basing our model para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 55 publications
(32 reference statements)
1
53
0
Order By: Relevance
“…For instance, a large part of the intraspecific variability in shelled mollusks could be caused by differences in growth rates (Urdy et al 2010a) and development 9 Ammonoid Intraspecific Variability Crônier 2003, 2005). This could also explain certain recurrent patterns in intraspecific variation in the shells of ammonoids and other mollusks with coiled shells (e.g., Dommergues et al 1989;Urdy et al 2010bUrdy et al , 2013Urdy 2015). Extant cephalopods can comprise a high intraspecific variability, particularly in their variable size-at-age, which can be related to intrinsic as well as extrinsic (environmental) factors (Boyle and Boletzky 1996;compare De Baets et al 2015a; Keupp and Hoffmann 2015 for pathologies affecting growth).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a large part of the intraspecific variability in shelled mollusks could be caused by differences in growth rates (Urdy et al 2010a) and development 9 Ammonoid Intraspecific Variability Crônier 2003, 2005). This could also explain certain recurrent patterns in intraspecific variation in the shells of ammonoids and other mollusks with coiled shells (e.g., Dommergues et al 1989;Urdy et al 2010bUrdy et al , 2013Urdy 2015). Extant cephalopods can comprise a high intraspecific variability, particularly in their variable size-at-age, which can be related to intrinsic as well as extrinsic (environmental) factors (Boyle and Boletzky 1996;compare De Baets et al 2015a; Keupp and Hoffmann 2015 for pathologies affecting growth).…”
Section: Introductionmentioning
confidence: 99%
“…While exact growth rates of ammonoids are unknown, some researchers have concluded that heterochrony (changes in the timing and rate of developmental traits during ontogeny) may play an important role in creating new species (Gould, 1977;Alberch et al, 1979;Landman and Geyssant, 1993;Yacobucci, 1999;Harada and Tanabe, 2005;Gangopadhyay and Bardhan, 2007;Korn et al, 2013). Alternatively, differing paleoecological factors during the existence of any species may account for a broad spectrum of morphological variation, which has been documented recently in several studies on extant and extinct mollusks; see Urdy et al (2010) and Wilmsen and Mosavinia (2011) for examples. Most likely, both ecophenotypic and genetic variability play a role in creating variation within a species; however, before researchers can distinguish the controls and effects of these two mechanisms, a new methodology is necessary to quantify the spectrum of variation present within a species.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in mollusc shell morphology can be both genetically and environmentally determined. However, although there is an extensive literature on correlations between some environmental aspects and mollusc shell shapes (Urdy et al 2010b), the contribution of local adaptation to morphological differentiation of bivalve populations is still poorly studied (Costa et al 2008). In this context, further research should focus on the phenotypic variation and morphological plasticity of the shell of E. siliqua as a function of different environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%